2021
DOI: 10.1111/jfpp.15184
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of chia ( Salvia hispanica L.) oil incorporated with astaxanthin

Abstract: Ingest of astaxanthin and omega‐3 fatty acids is related to several health benefits. Chia oil is one of the principal sources of α‐linolenic acid (ALA) belonging to the omega‐3 fatty acids. This work evaluated the stability of blends of chia oil and astaxanthin (400 µg/g oil) during storage at 25, 45, and 65°C during 35, 16, and 4 days, respectively. The effect of α‐tocopherol addition (100 µg/g oil) was also evaluated. The highest antioxidant activity (2.29 ± 0.11 µmol Trolox/g oil) was observed in oil added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…Conversely, Espinaco et al. [ 13 ] found that the addition of ASX or VE to CO promoted higher PV than those observed for CO alone when storing at 25 and 45°C. In this case, they added antioxidants to CO at lower concentrations (400 ppm) than those used in our work (2000 ppm).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Conversely, Espinaco et al. [ 13 ] found that the addition of ASX or VE to CO promoted higher PV than those observed for CO alone when storing at 25 and 45°C. In this case, they added antioxidants to CO at lower concentrations (400 ppm) than those used in our work (2000 ppm).…”
Section: Resultsmentioning
confidence: 97%
“…Espinaco et al. [ 13 ] studied the stability of unencapsulated CO with ASX alone (400 mg kg −1 oil), or ASX in combination with αT (400 + 100 mg kg −1 oil) during 35 days of storage at 25°C. They reported PV higher than 20 meq kg −1 oil for CO–ASX system and PV close to 70 meq kg −1 oil for CO–ASX + αT combination, which demonstrates a prooxidant effect for the mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Astaxanthin content was determined using first‐order derivate spectrophotometry. [ 24 ] First, 0.15 mL of the oleoresin extract previously obtained was mixed with 0.15 mL of ethanol and 1.2 mL of ethyl acetate:ethanol (1:1). Samples were scanned at 400–700 nm and first‐order derivate spectrum was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…This previous step is necessary to favor protein interaction with calcium. [19,20] Given that the mixture of astaxanthin and chia oil is a promising strategy to exert a synergistic benefit of both bioactive compounds, [21][22][23][24] and that WPA can provide complementary properties to alginate when using as wall material, [12,20] this encapsulation system should be investigated due to the scarce information available in the literature to the best of our knowledge. Therefore, this study aimed to encapsulate chia oil-astaxanthin blends using the cold ionic gelation method and to evaluate the effect of WPA on the storage stability of chia oil-astaxanthin blends encapsulated in alginate gel beads.…”
Section: Introductionmentioning
confidence: 99%